Pengaruh Waktu Fermentasi Bakteri Asam Laktat Dari Sari Kulit Buah Naga Merah (Hylocereus Polyrhizus) Terhadap Aktivitas Bakteri Propionibacterium acne: Effect of Lactic Acid Bacteria Fermentation Time from Red Dragon Fruit Peel Juice (Hylocereus Polyrhizus) on the Activity of Propionibacterium acne - Cindy Puspita Perdana; M. Arifuddin; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Fermentation of lactic acid bacteria from Red Dragon Fruit peel extract (Hylocereus polyrhizus) produces bacteriocins that can inhibit the growth of pathogenic bacteria. The purpose of this research is to the Red Dragon Fruit peel extract that has been fermented using lactic acid bacteria has the potential to inhibit the growth of Propionibacterium acne bacteria. The method includes the process of extracting samples and pasteurizing the juice and then proceeding with the fermentation process with variations in time of 3 days, 7 days, 12 days, and 14 days at 37?C. Antibacterial testing was carried out using the good method. The results showed that there was an effect of fermentation time on a low pH value of 3.98. As well as antibacterial testing can inhibit the growth of propionibacterium acne bacteria with the largest inhibition zone shown in the 7th day fermented extract at a concentration of 50% at 22.72 mm, a concentration of 75% is 22.99 mm, and a concentration of 100% is 25.97 mm.